2016
DOI: 10.1590/0103-656420150015
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de necessidades de intervenção psicológica: um estudo-piloto no ensino superior português

Abstract: Resumo Este estudo analisa as necessidades de intervenção psicológica dos estudantes da Faculdade de Ciências Humanas da Universidade Católica Portuguesa. Participaram 157 alunos, avaliados nas suas preocupações e necessidades pessoais, de carreira e de aprendizagem, bem como nas preferências relativas ao apoio, por meio do questionário de identificação de necessidades de intervenção psicológica. Os resultados indicam necessidade de apoio nas áreas: (i) controlo de ansiedade e nervosismo, (ii) medo de falhar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
2
4
0
5
Order By: Relevance
“…Exceptions included items such as "increasing self-confidence", "increasing motivation", "fear of failure", "Controlling anxiety and nervousness", and "test anxiety", related to Self-Relation Needs; "overcoming procrastination", "improving study skills", "job search strategies", and "time management skills", related to Study and Work Needs. As with previous studies in Portugal (Pinto, et al, 2016), this sample expresses low support needs. These results are lower than those obtained by previous international studies, which found that the psychological intervention needs felt by students were generally higher (e.g., Gallagher et al, 1992;Hinderaker, 2003;Nicholas, 1995).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Exceptions included items such as "increasing self-confidence", "increasing motivation", "fear of failure", "Controlling anxiety and nervousness", and "test anxiety", related to Self-Relation Needs; "overcoming procrastination", "improving study skills", "job search strategies", and "time management skills", related to Study and Work Needs. As with previous studies in Portugal (Pinto, et al, 2016), this sample expresses low support needs. These results are lower than those obtained by previous international studies, which found that the psychological intervention needs felt by students were generally higher (e.g., Gallagher et al, 1992;Hinderaker, 2003;Nicholas, 1995).…”
Section: Discussionsupporting
confidence: 80%
“…Compared with previous generations, current university students are more diversified, especially in terms of sex, age, and nationality (Pinto, Faria, Pinto, and Taveira, 2016). Therefore, this reality poses greater challenges to the psychological intervention services of higher education institutions.…”
mentioning
confidence: 99%
“…A satisfação académica tem sido considerada um indicador de adaptação e bem-estar em ambientes de trabalho escolar, com uma relação positiva com a satisfação geral com a vida (e.g., Osti & Almeida, 2019;Sheu & Bordon, 2017). A satisfação com a vida académica reflete o processo de correspondência entre as expectativas, motivação e envolvimento dos estudantes e as expectativas e resposta das instituições de ensino em relação aos mesmos (Arantes et al, 2018;Fernandez et al, 2017;Zannon, 2011 (Souza & Reinert, 2010), e as necessidades de apoio por parte dos estudantes (Pinto et al, 2016).…”
Section: Discussionunclassified
“…A experiência académica dos estudantes do Ensino Superior é comumente marcada por um conjunto diversificado de perceções que moldam o seu grau de satisfação. Essa experiência académica envolve o acesso e utilização dos espaços, equipamentos e recursos da instituição, a aprendizagem e rendimento académico, a organização do curso e ensino dos professores, as relações com os colegas e os serviços de apoio (Astin, 1993;Casanova, Esteban, Cervero, Bernardo, & Almeida, 2017;Fernández, Araújo, Vacas, Almeida, & Gonzalez, 2017;Grebennikov & Shah, 2013;Pinto, Faria, Pinto, & Taveira, 2016). A satisfação é determinada por variáveis relativas à instituição, curso, relações interpessoais, perspetiva de carreira e caraterísticas pessoais (Hu & Kuh, 2002;Pinto et al, 2016), nomeadamente quando as expectativas iniciais ou as necessidades dos estudantes se concretizam, face à realidade académica (Lent et al, 2005;Lent, Taveira, Sheu, & Singley, 2009;Pinto, Quadros, Cruz, & Conrad, 2017;Soares et al, 2018;Souza & Reinert, 2010;Tomás & Gutiérrez, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation